Nutritional and antioxidant status by skin types among female adults - Bae, Hyun Sook (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2010)
This study was performed to analyze the relationship among sebum · hydration content of the skin and nutritional intake, serum antioxidant minerals and antioxidant enzymes, and lipid peroxide concentration in 50 female subjects in their 20s. The skin type was divided into Dry Skin, Mixed Skin, and Oily Skin, and the dry skin group was 14%, the mixed skin group was 56%, and the oily skin group was 30% of all subjects. The average age of the subjects was 20.54 ± 1.43 years and BMI was 20.66. The average sebum content in each group was in the order of T-zone>forehead>chin>cheek. In case of the T-zone, a significant difference between the dry skin group and the oily skin group was observed, suggesting that the area is most sensitive to sebum content by skin type. Significant differences were not observed in energy and nutrient intakes by skin type. Serum concentrations of antioxidant minerals such as copper, manganese, zinc and selenium were not significantly different among the groups, but the dry skin group tended to be higher than the oily skin group. Serum catalase was significantly higher in the oily skin group (P < 0.05), and MDA was significantly higher in the mixed skin group (P < 0.05). The hydration of the cheek and serum zinc showed a negative correlation, and the sebum content of the cheek and GPx showed a significant negative correlation. The hydration of the forehead and serum copper showed a significant negative correlation, and the hydration of the forehead and GPx showed a significant positive correlation. The hydration of the chin and serum SOD showed a significant positive correlation. With these results, it is considered that the basic condition of nutritional status can affect the skin health.